Film-like adhesive with cut crystal film, electronic component using same, and method for producing same

By optimizing the energy storage modulus and the combination of the cut-crystal film of the film-like adhesive, combined with the ratio of epoxy resin and phenoxy resin, the chip flying problem is solved, and electronic components with high transparency and high productivity are achieved manufacture.

CN119234295APending Publication Date: 2024-12-31FURUKAWA ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480002252.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-28
Filing Date
2024-04-18
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the cutting process of electronic components, the film-shaped adhesive with a cut crystal film can easily cause chips to fly out after reducing the mixing amount of particulate additives such as fillers, affecting production efficiency and product quality.

Method used

By designing the energy storage modulus E1 of the film-like adhesive and the energy storage modulus E2 of the cut-crystal film, it satisfies E1×E2≥7.0, and the light transmittance reaches more than 60% after curing, combining with epoxy resin and phenoxy group. The ratio of resin and filler material is to use a thermal cationic polymerization initiator as a curing agent to control the transparency and rigidity of the adhesive and inhibit the chip from flying out.

Benefits of technology

It effectively suppresses chip flight, ensures high productivity in the cutting process, and provides high transparency and excellent optical properties after curing, making it suitable for assembly of transparent film chips.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234295A_ABST
    Figure CN119234295A_ABST
Patent Text Reader

Abstract

Provided is a film-like adhesive with a cut crystal film, comprising: a cut crystal film having a base material and an adhesive layer; and a film-like adhesive disposed on the adhesive layer, in which the storage modulus E1 (MPa) of the film-like adhesive at 60 DEG C and the storage modulus E2 (MPa) of the dicing film at 60 DEG C satisfy E1 * E2 > = 7.0, and the light transmittance of a cured product of the film-like adhesive is 60% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a film-like adhesive with a cut wafer film, an electronic component using the film-like adhesive with a cut wafer film, and a method for producing the electronic component. Background Art

[0002] Image sensors (imaging elements) such as CMOS (Complementary Metal Oxide Semiconductor) image sensors and CCD (Charge Coupled Device) image sensors are installed in digital cameras, digital video cameras and other photographic equipment. The image sensor uses a photodiode to perform photoelectric conversion on the incident light and convert it into an electrical signal, and forms a digital image after signal processing. Color filters, microlenses, etc. are arranged on the surface of the photodiode as needed, and a transparent protective film such as a glass plate is usually arranged on its surface. Such a transparent protective film is fixed by a film-like adhesive or the like. The adhesive used for bonding and fixing the transparent protective film of the image sensor is required to have transparency that allows light to pass through at least after the curing reaction.

[0003] Film adhesives themselves are known to have various compositions, and are widely used not only in image sensors but also in the manufacture of electronic devices and their components, etc. For example, in the manufacturing process of semiconductor chips, film adhesives are used as die-bonding films.

[0004] The following scheme is proposed: a film-like adhesive that shows sufficiently high transparency at least after a curing reaction is used as a laminated structure with a cut crystal film (a film-like adhesive with a cut crystal film) for the manufacture of electronic components. For example, Patent Document 1 describes a method for manufacturing electronic components, which includes: a first step of obtaining a laminated body in which a transparent film-like component, a film-like adhesive that shows sufficiently high transparency after a curing reaction, and a cut crystal film are sequentially laminated; a second step of cutting the transparent film-like component and the film-like adhesive as a whole to obtain a transparent film-like chip with an adhesive layer on the cut crystal film; a third step of removing the cut crystal film from the adhesive layer and thermally pressing the transparent film-like chip with the adhesive layer and other components constituting the electronic component by means of the adhesive layer; and a fourth step of thermally curing the adhesive layer. The transparent film member may be a glass substrate, a transparent resin, or the like. The transparent film chip with an adhesive layer obtained by cutting the transparent film member into a desired shape as described above can be assembled into an electronic component, for example, as a protective film for a photodiode, by means of a cured product of the adhesive layer.

[0005] Furthermore, the film-like adhesive with a dicing film can be used as a dicing adhesive film in the manufacturing process of semiconductor chips to provide the adhesive for dicing of a semiconductor wafer and for individualizing semiconductor chips by dicing.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2023 / 026584 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the above-mentioned dicing process, a lot of chips separated by dicing may be peeled off from the film adhesive during dicing (chip flying out). The inventors have repeatedly conducted research and found that when the mixing amount of particulate additives such as fillers is reduced in order to improve the transparency of the film adhesive, chip flying out in the dicing process is more likely to occur.

[0011] The present invention aims to provide a film adhesive with a cut crystal film, wherein the film adhesive shows sufficiently high transparency at least after the curing reaction, and can effectively suppress the chip from flying out during the dicing process. In addition, the present invention aims to provide a method for manufacturing an electronic component using the film adhesive with a cut crystal film.

[0012] Means for solving problems

[0013] The above-mentioned problems of the present invention are solved by the following means. [1]

[0015] A film-like adhesive with a cut wafer film, comprising: a cut wafer film having a substrate and an adhesive layer; and a film-like adhesive disposed on the adhesive layer.

[0016] The storage modulus E1 (MPa) of the film adhesive at 60°C and the storage modulus E2 (MPa) of the cut-wafer film at 60°C satisfy E1×E2≥7.0,

[0017] The cured product of the film-like adhesive has a light transmittance of 60% or more. [2]

[0019] The film-like adhesive with a cut wafer film as described in [1], wherein the film-like adhesive contains an epoxy resin and a phenoxy resin. [3]

[0021] The film-like adhesive with a sliced ​​film according to [1] or [2], wherein the film-like adhesive contains a filler, and the content of the filler is 10% by mass or less of the total solid content of the film-like adhesive. [4]

[0023] The film-like adhesive with a cut wafer film as described in [3], wherein the particle size (d50) of the filler is 500 nm or less. [5]

[0025] The film-like adhesive with a cut wafer film as described in any one of [1] to [4], wherein the film-like adhesive contains a curing agent, and the curing agent is a thermal cationic polymerization initiator. [6]

[0027] The film-like adhesive with a cut wafer film as described in any one of [1] to [5], wherein E1 is 0.1 MPa to 1.0 MPa, and E2 is 10 MPa to 70 MPa. [7]

[0029] A method for manufacturing an electronic component, the method comprising:

[0030] In a first step, a laminate is obtained in which a transparent film-like member and the film-like adhesive with a cut wafer film according to any one of [1] to [6] are sequentially laminated.

[0031] The second step is to cut the transparent film member and the film adhesive integrally, thereby obtaining a transparent film chip with an adhesive layer on the cut film;

[0032] A third step is to remove the cut wafer film from the adhesive layer, and to thermally press-bond the transparent film-shaped chip with the adhesive layer to other members constituting the electronic component via the adhesive layer; and

[0033] In the fourth step, the adhesive layer is thermally cured. [8]

[0035] The method for manufacturing an electronic component as described in [7], wherein the electronic component is an image sensor. [9]

[0037] The method for manufacturing an electronic component according to [8], wherein the electronic component has a structure in which the transparent film-like chip is incorporated as a protective film of a photodiode.

[0038] In the present invention, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0039] In the present invention, when described as "a compound", it means a "compound having a skeleton of" For example, "a dicyandiamide compound" means not only dicyandiamide itself but also a compound in which at least a part of the hydrogen atoms in dicyandiamide are substituted.

[0040] Effects of the Invention

[0041] In the film adhesive with a wafer-cutting film of the present invention, the film adhesive shows sufficiently high transparency at least after the curing reaction, and can effectively suppress the chip from flying out when applied to the cutting process. In addition, according to the manufacturing method of the electronic component of the present invention, the chip flying out of the transparent film chip obtained in the cutting process can be effectively suppressed, and as a result, an electronic component assembled with a transparent film chip by a transparent cured product of the film adhesive can be obtained with high productivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a cross-sectional view schematically showing the structure of a film-like adhesive with a release film prepared in Examples. DETAILED DESCRIPTION

[0043] [Film-like adhesive with cut-wafer film]

[0044] The film adhesive with a cut crystal film of the present invention comprises: a cut crystal film having a substrate and an adhesive layer; and a film adhesive disposed on the adhesive layer. In addition, the storage modulus E1 (MPa) of the film adhesive at 60°C and the storage modulus E2 (MPa) of the cut crystal film at 60°C satisfy E1×E2≥7.0, and the light transmittance of the film adhesive after curing is 60% or more.

[0045] By making the storage moduli E1 and E2 satisfy the above relationship, even when the film adhesive with the cut crystal film of the present invention is locally heated by the friction heat of the blade during cutting (it will be heated to about 60°C), the rigidity of the film adhesive with the cut crystal film of the present invention as a whole can be ensured, and the chip flying out can be effectively suppressed. After the curing reaction, it shows high transparency, and thus it shows excellent optical properties as an adhesive when the transparent film member is assembled into electronic components, etc. It can be considered that since the storage modulus of the integrated body that combines the cut crystal film and the film adhesive is controlled, even if a film adhesive layer whose storage modulus becomes smaller due to reducing the mixing amount of the microparticle additive is used, the storage modulus of the cut crystal film as a whole can be appropriately controlled, and vibration during cutting, etc. can be suppressed.

[0046] In the present invention, from the perspective of suppressing chip flying out, the storage modulus E1 (MPa) of the film adhesive at 60°C and the storage modulus E2 (MPa) of the cut crystal film at 60°C are preferably E1×E2≥10.0, more preferably E1×E2≥11.0, further preferably E1×E2≥12.0, and particularly preferably E1×E2≥15.0. The upper limit is not particularly limited, and is usually 50.0≥E1×E2, and is actually 40.0≥E1×E2. Therefore, it is preferably 50.0≥E1×E2≥7.0, more preferably 50.0≥E1×E2≥10.0, further preferably 50.0≥E1×E2≥11.0, further preferably 50.0≥E1×E2≥12.0, and particularly preferably 40.0≥E1×E2≥15.0.

[0047] The storage modulus E1 of the film adhesive at 60° C. is not particularly limited as long as the relationship between E1 and E2 is satisfied. E1 is preferably 0.1 MPa to 1.5 MPa, more preferably 0.1 MPa to 1.0 MPa, further preferably 0.2 MPa to 1.0 MPa, further preferably 0.3 MPa to 0.9 MPa, further preferably 0.3 MPa to 0.8 MPa.

[0048] The storage modulus E2 of the cut film at 60° C. is not particularly limited as long as the relationship between E1 and E2 is satisfied. E2 is preferably 10 MPa to 80 MPa, more preferably 10 MPa to 70 MPa, further preferably 20 MPa to 70 MPa, further preferably 25 MPa to 60 MPa, further preferably 30 MPa to 50 MPa.

[0049] The storage modulus E1 of the film adhesive at 60° C. can be controlled by the types and contents of the components (resin, curing agent, filler, etc.) constituting the film adhesive.

[0050] The storage modulus E2 of the above-mentioned cut film at 60°C can be controlled by the type and content of the components constituting the cut film (resins constituting the adhesive layer and the substrate), the thickness of the adhesive layer and the substrate, etc. Usually, the substrate has a greater thickness than the adhesive layer, so E2 tends to be greatly affected by the characteristics of the substrate. From this aspect, the storage modulus E3 of the substrate of the cut film at 60°C is preferably 10MPa to 80MPa, more preferably 10MPa to 70MPa, further preferably 20MPa to 70MPa, further preferably 30MPa to 60MPa, and further preferably 30MPa to 50MPa.

[0051] The storage modulus E1 of the film adhesive at 60°C and the storage modulus E2 of the cut film at 60°C can be determined by the methods described in the Examples. In addition, the storage modulus E3 of the substrate at 60°C can also be determined by the method for determining the storage modulus E2 of the cut film at 60°C.

[0052] The film adhesive constituting the film with a cut crystal film of the present invention has a light transmittance of 60% or more after curing. By making the transmittance after curing 60% or more, transparency can be ensured after curing, and optical properties suitable for bonding transparent film components and the like can be exerted. Here, in the present invention, "a light transmittance of 60% or more" means a light transmittance of 60% or more at a wavelength of 400nm. The light transmittance at a wavelength of 400nm represents the light transmittance at wavelengths in the entire visible light region.

[0053] "The cured product of the film adhesive" refers to a cured product obtained by treating the film adhesive at 150°C for 1 hour. It should be noted that in the present invention or the specification, when the "film adhesive" is simply referred to in the description of the characteristics of the film adhesive, it refers to the film adhesive before thermal curing. Specifically, it refers to a film adhesive that is not exposed to a temperature higher than the temperature at which the epoxy resin undergoes thermal curing after the film adhesive is prepared. Preferably, it is a film adhesive that is not exposed to a temperature condition higher than 25°C after the film adhesive is prepared. It should be noted that the above description is for clarifying the characteristics of the film adhesive, and the film adhesive with a cut crystal film of the present invention is not limited to the film adhesive that is not exposed to a temperature condition higher than 25°C.

[0054] The light transmittance of the cured product of the film adhesive is more preferably 70% or more, further preferably 80% or more, further preferably 85% or more. The light transmittance of the cured product of the film adhesive is preferably 70% to 95%, more preferably 80% to 92%, further preferably 85% to 90%.

[0055] The light transmittance of the cured product of the film-like adhesive is determined by the method described in Examples.

[0056] The light transmittance of the cured product of the film adhesive can be controlled by the types and contents of the components (resin, curing agent, filler, etc.) of the film adhesive. The filler not only has an influence on the light transmittance by its content but also by its particle size.

[0057] The transparency of the film-like adhesive before curing is not limited, and it may be transparent or opaque. Therefore, the light transmittance of the film-like adhesive before curing at a wavelength of 400 nm may be 60% or more, or less than 60%.

[0058] Hereinafter, the film-like adhesive with a cut wafer film of the present invention will be described in more detail.

[0059] <Cut film>

[0060] The cut film constituting the film-like adhesive with cut film of the present invention has a base material and an adhesive layer.

[0061] The materials and compositions of the substrate and the adhesive layer are not particularly limited as long as they satisfy the above-mentioned E1 and E2 when combined with a film-like adhesive after being laminated to form a cut-wafer film.

[0062] -Base Material-

[0063] The substrate can be made of various resin materials. Among them, it is preferably made of a resin material selected from polyolefin resins and polyvinyl chloride resins. These resin materials also preferably have a cross-linked structure. The bond that contributes to the formation of the cross-linked structure can be a covalent bond, a bond based on ionic interaction, or a hydrogen bond.

[0064] Examples of the polyolefin resin include polyethylene, polypropylene, ethylene-propylene copolymers, poly-1-butene, poly-4-methyl-1-pentene, ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid alkyl ester copolymers (ethylene-ethyl acrylate copolymers, ethylene-methyl acrylate copolymers, ethylene-methyl methacrylate copolymers, etc.), ethylene-(meth)acrylic acid copolymers, ionomer resins and other α-olefin homopolymers or copolymers thereof, and mixtures thereof.

[0065] It is particularly preferred that the cohesive force generated by the metal ions is used to make a polymer into a cohesive body of a synthetic resin, i.e., an ionomer resin. For example, an ionomer resin obtained by crosslinking an ethylene-(meth)acrylic acid binary copolymer or an ethylene-(meth)acrylic acid-(meth)acrylic acid alkyl ester ternary copolymer with metal ions can be exemplified. These resins are suitable for the expansion process in terms of uniform expansibility. The metal ions contained in the above-mentioned ionomer resin are not particularly limited, and zinc ions, sodium ions, etc. can be cited. Zinc ions are preferred from the perspective of low solubility and low contamination.

[0066] Generally, ionomer resin has a greater restoring force to stretching than a resin without metal ions, and has a greater shrinkage stress when heat is applied to the stretched state after the expansion process. Therefore, ionomer resin is preferred in that a heat shrinking process can be performed, which removes the slack generated in the tape after the expansion process by heat shrinking, thereby tightening the tape and stably maintaining the interval between the wafer chips.

[0067] In addition to the above ionomer resins, thermoplastic crosslinked resins obtained by crosslinking a resin selected from low-density polyethylene having a specific gravity of 0.910 or more and less than 0.930, ultra-low-density polyethylene having a specific gravity of less than 0.910, and ethylene-vinyl acetate copolymers are also preferred.

[0068] As a method of cross-linking, there can be cited a method of irradiating the above-mentioned resin with energy rays such as electron beams. Such a thermoplastic cross-linked resin has a certain uniform expansibility because the cross-linked part and the non-cross-linked part coexist in the resin. In addition, such a thermoplastic cross-linked resin contains almost no chlorine atoms in the molecular chain structure, so even if the unnecessary belt is incinerated after use, chlorinated aromatic hydrocarbons such as dioxins or their analogs will not be generated, and the environmental burden is also small. By appropriately adjusting the amount of energy rays irradiated on the above-mentioned polyethylene and ethylene-vinyl acetate copolymer, a resin with sufficient uniform expansibility can be obtained.

[0069] The substrate may be a single layer or a multi-layer.

[0070] The substrate is preferably an ionomer resin of ethylene-(meth)acrylic acid copolymer.

[0071] The thickness of the substrate is not particularly limited, but is preferably 50 μm to 200 μm, more preferably 60 μm to 160 μm, and even more preferably 70 μm to 150 μm.

[0072] - Adhesive layer -

[0073] The adhesive layer constituting the adhesive tape of the present invention is not particularly limited as long as it has the property of being able to retain the laminate of the transparent film-like member (adherend) and the film-like adhesive described later to prevent peeling during the cutting process and being able to be peeled off from the transparent film-like chip with the adhesive when picking up.

[0074] The adhesive constituting the adhesive layer is not particularly limited as long as it exhibits the above-mentioned properties, and a common adhesive used in the application of the wafer film, such as an acrylic adhesive, a rubber adhesive, etc., can be appropriately used. Among them, an energy-ray-curable adhesive is preferred. If it is an energy-ray-curable adhesive, it is easy to pick up by curing it before the picking-up process. Here, energy rays refer to ionizing radiation such as ultraviolet rays or electron beams.

[0075] As the adhesive constituting the adhesive layer, a common adhesive used as an adhesive for dicing adhesive tape can be used without particular limitation. As for the composition, characteristics, and manufacturing method of the adhesive, for example, reference can be made to paragraphs

[0039] to

[0076] of Japanese Patent Gazette No. 6928852, paragraphs

[0033] to

[0052] of Japanese Patent Gazette No. 6989561, and paragraphs

[0031] to

[0057] of Japanese Patent Gazette No. 2023-13022.

[0076] The adhesive constituting the adhesive layer preferably contains an acrylic adhesive containing a (meth) acrylic resin as a base polymer, and more preferably contains an acrylic adhesive containing at least one of an alkyl (meth) acrylate and (meth) acrylic acid as a constituent component. The alkyl (meth) acrylate preferably further has a radiation-curable group introduced into the side chain, and more preferably has a (meth) acrylate having an isocyanate group added thereto. The adhesive may further contain a radiation-curable oligomer, such as a urethane (meth) acrylate oligomer, and the like.

[0077] The adhesive layer may contain a curing agent. Examples of the curing agent include polyisocyanate compounds.

[0078] In addition, the pressure-sensitive adhesive layer may contain a photopolymerization initiator.

[0079] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but is preferably 2 μm to 35 μm, more preferably 5 μm to 30 μm, and even more preferably 5 μm to 20 μm.

[0080] <Film Adhesive>

[0081] The film-like adhesive constituting the film-like adhesive with a cut wafer film of the present invention will be described.

[0082] As the film-like adhesive, any common film-like adhesive may be used as long as it satisfies the above-mentioned E1 and E2 when combined with the cut wafer film and the light transmittance of the cured product of the film-like adhesive is 60% or more.

[0083] The film-like adhesive preferably contains an epoxy resin and a polymer component, more preferably contains an epoxy resin and a urethane resin, or an epoxy resin and a phenoxy resin, and further preferably contains an epoxy resin and a phenoxy resin.

[0084] The film adhesive may contain a filler. However, from the perspective of improving light transmittance, the content of the filler when the film adhesive contains the filler is preferably 30% by mass or less of the total solid content of the film adhesive, more preferably 20% by mass or less, further preferably 10% by mass or less, and further preferably 5% by mass or less.

[0085] Film adhesives usually contain a curing agent.

[0086] In a preferred embodiment of the present invention, the film adhesive preferably contains an epoxy resin, a polymer component, and a curing agent. In this case, as described above, a filler may be contained. Each component is described below.

[0087] -Epoxy resin-

[0088] The epoxy resin is a thermosetting resin having an epoxy group, and the epoxy equivalent is 1000 g / eq or less. The epoxy resin may be any of a liquid, a solid or a semi-solid. In the present invention, a liquid means a softening point of less than 25°C, a solid means a softening point of 60°C or more, and a semi-solid means a softening point between the softening point of the liquid and the softening point of the solid (25°C or more and less than 60°C). The epoxy resin used in the present invention preferably has a softening point of 100°C or less from the perspective of obtaining a film-like adhesive that can achieve a low melt viscosity in a suitable temperature range (e.g., 60°C to 120°C). It should be noted that in the present invention, the softening point is a value measured by a softening point test (ring and ball) method (measurement conditions: in accordance with JIS-K7234 1986).

[0089] The epoxy resin used in the present invention preferably has an epoxy equivalent of 150 to 800 g / eq from the viewpoint of increasing the crosslinking density of the thermosetting body. In the present invention, the epoxy equivalent refers to the number of grams (g / eq) of the resin containing 1 gram equivalent of epoxy groups.

[0090] The weight average molecular weight of the epoxy resin is usually preferably less than 10000, more preferably not more than 5000. The lower limit is not particularly limited, but is generally 300 or more.

[0091] The weight average molecular weight is a value obtained by GPC (gel permeation chromatography) analysis.

[0092] As the skeleton of epoxy resin, for example, phenol novolac type, o-cresol novolac type, cresol novolac type, dicyclopentadiene type, biphenyl type, fluorene bisphenol type, triazine type, naphthol type, naphthyl diol type, triphenylmethane type, tetraphenyl type, bisphenol A type, bisphenol F type, bisphenol AD ​​type, bisphenol S type and trimethylolmethane type etc. can be cited. Among them, from the aspect of obtaining a film-like adhesive with low crystallinity of the resin and good appearance, preferably triphenylmethane type, bisphenol A type, cresol novolac type or o-cresol novolac type. They can be used alone or in combination of two or more, preferably a combination of triphenylmethane type and bisphenol A type.

[0093] In the total content of 100 parts by mass of the components (specifically, components other than the solvent, i.e., solid components) constituting the film-like adhesive, the content of the epoxy resin is preferably 25 to 80 parts by mass, more preferably 30 to 80 parts by mass, further preferably 30 to 70 parts by mass, further preferably 40 to 70 parts by mass. By making the content within the above-mentioned preferred range, storage stability and transparency can be improved. In addition, by being below the above-mentioned preferred upper limit, the generation of oligomer components can be suppressed, and changes in the film state (film viscosity, etc.) can be difficult to occur when the temperature changes slightly.

[0094] The content of the epoxy resin in 100 parts by mass of the total content of the epoxy resin and the polymer component is preferably 30 parts by mass to 70 parts by mass, and more preferably 30 parts by mass to 60 parts by mass.

[0095] -Polymer components-

[0096] As the above-mentioned polymer component, as long as it is a component that suppresses the film viscosity at room temperature (25°C) when forming a film-like adhesive (even if a small amount of temperature changes, the film state is easy to change), and gives sufficient adhesion and film-forming properties (film forming properties). For example, natural rubber, butyl rubber, isoprene rubber, chloroprene rubber, ethylene-vinyl acetate copolymer, polybutadiene resin, polycarbonate resin, thermoplastic polyimide resin, polyamide resins such as 6-nylon or 6,6-nylon, phenoxy resin, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyamide-imide resin, polyurethane resin, etc. can be cited. These polymer components can be used alone, or two or more can be used in combination. As a polymer component, at least one of a phenoxy resin and a polyurethane resin is preferred.

[0097] The weight average molecular weight of the polymer component is not less than 10000. The upper limit is not particularly limited, but is practically not more than 5000000.

[0098] The weight average molecular weight of the polymer component is a value obtained by polystyrene conversion using GPC (Gel Permeation Chromatography). The same applies to the specific weight average molecular weight of the polymer component below.

[0099] The glass transition temperature (Tg) of the polymer component is preferably less than 100°C, more preferably less than 90°C. The lower limit is preferably 0°C or more, more preferably 10°C or more. Therefore, the glass transition temperature (Tg) of the polymer component is preferably 0°C or more and less than 100°C.

[0100] The glass transition temperature of the polymer component is the glass transition temperature measured by a differential scanning calorimeter (DSC) at a heating rate of 0.1°C / min. More specifically, the temperature is raised to -100°C to 100°C at a heating rate of 0.1°C / min, and the extrapolated glass transition starting temperature of JIS K7121:2012 "Method for Determination of Transition Temperature of Plastics" is used as the glass transition temperature. The values ​​of the specific glass transition temperatures of the polymer components are also the same below.

[0101] It should be noted that in the present invention, resins having epoxy groups such as phenoxy resins in epoxy resins and polymer components refer to resins having epoxy equivalents of 1000 g / eq or less as epoxy resins, and resins having epoxy equivalents exceeding 1000 g / eq as polymer components.

[0102] (Phenoxy resin)

[0103] Since the structure of phenoxy resin is similar to that of epoxy resin, it is preferable as a polymer component from the viewpoint of good compatibility. If a phenoxy resin is contained, the effect of excellent adhesiveness can be exhibited.

[0104] The phenoxy resin can be obtained by a conventional method. For example, the phenoxy resin can be obtained by the reaction of a bisphenol or biphenol compound with an epihalohydrin such as epichlorohydrin, or by the reaction of a liquid epoxy resin with a bisphenol or biphenol compound.

[0105] The weight average molecular weight of the phenoxy resin is preferably 10,000 or more, more preferably 10,000 to 100,000.

[0106] The amount of epoxy groups remaining in the phenoxy resin in small amounts is preferably 5000 g / eq or more in terms of epoxy equivalent.

[0107] The glass transition temperature (Tg) of the phenoxy resin is preferably less than 100° C., more preferably less than 90° C. The lower limit is preferably 0° C. or more, more preferably 10° C. or more. Therefore, the glass transition temperature (Tg) of the phenoxy resin is preferably 0° C. or more and less than 100° C.

[0108] (Polyurethane resin)

[0109] Polyurethane resin is a polymer having a carbamate (urethane) bond in the main chain. Polyurethane resin has a structural unit derived from a polyol and a structural unit derived from a polyisocyanate, and may also have a structural unit derived from a polycarboxylic acid. Polyurethane resins may be used alone or in combination of two or more.

[0110] The Tg of the polyurethane resin is usually 100°C or lower, preferably 60°C or lower, more preferably 50°C or lower, and also preferably 45°C or lower.

[0111] The weight average molecular weight of the polyurethane resin is not particularly limited, but generally, a polyurethane resin in the range of 5,000 to 500,000 is used.

[0112] The polyurethane resin can be synthesized by a conventional method or can be obtained from the market. Examples of commercially available products that can be used as the polyurethane resin include Dynaleo VA-9320M, Dynaleo VA-9310MF, and Dynaleo VA-9303MF (all manufactured by TOYOCHEM).

[0113] The content of the polymer component relative to 100 parts by mass of the epoxy resin is preferably 1 to 250 parts by mass, more preferably 10 to 180 parts by mass, and further preferably 40 to 150 parts by mass. By making the content within this range, the rigidity and flexibility of the film adhesive before curing can be adjusted. The film state becomes good (the film viscosity is reduced), and the film fragility can also be suppressed.

[0114] The content of the polymer component in 100 parts by mass of the total content of the epoxy resin and the polymer component is preferably 30 parts by mass to 70 parts by mass, and more preferably 40 parts by mass to 70 parts by mass.

[0115] -Curing agent-

[0116] The curing agent is a component that affects the control of the light transmittance specified in the present invention. The curing agent is preferably selected in consideration of the control of the light transmittance.

[0117] As a curing agent, for example, amines, acid anhydrides and polyphenols can be mentioned. From the aspect of the storage stability of the film-like adhesive, it is preferred to use a latent curing agent. As a latent curing agent, for example, dicyandiamide compounds, imidazole compounds, curing catalyst composite polyphenol compounds, hydrazide compounds, boron trifluoride-amine complexes, amine imide compounds, polyamine salts and their modified substances or microcapsule-type latent curing agents can be mentioned, and they can be used alone or in combination of two or more. Among them, it is preferred to use at least one of dicyandiamide compounds, imidazole compounds and hydrazide compounds.

[0118] The latent curing agent may be a thermal cationic polymerization initiator, more preferably a sulfonium cation as a cationic component, a SbF6 - or PF6 - Thermal cationic polymerization initiator as anionic component.

[0119] From the perspective of showing a sufficient curing speed and ensuring transparency after curing, the content of the curing agent relative to 100 parts by mass of the epoxy resin is preferably 0.5 to 50 parts by mass, more preferably 1 to 40 parts by mass, further preferably 1 to 30 parts by mass, further preferably 1 to 10 parts by mass, further preferably 1 to 5 parts by mass.

[0120] -Filling material-

[0121] As the filler, any filler generally used in film adhesives can be used without particular limitation as long as the above light transmittance can be achieved. The filler is preferably an inorganic filler.

[0122] Examples of the inorganic filler include ceramics such as silica, clay, gypsum, calcium carbonate, barium sulfate, alumina, beryllium oxide, magnesium oxide, silicon carbide, silicon nitride, aluminum nitride, and boron nitride; metals such as aluminum, copper, silver, gold, nickel, chromium, lead, tin, zinc, palladium, and solder; or alloys; and carbons such as carbon nanotubes and graphene.

[0123] As the filler, silicon dioxide is preferred.

[0124] The particle size (d50) of the filler is not particularly limited, but is preferably 500 nm or less from the perspective of improving light transmittance. The particle size is preferably 1 nm to 500 nm, more preferably 10 nm to 500 nm, further preferably 10 nm to 499 nm, further preferably 10 nm to 450 nm, further preferably 10 nm to 350 nm, further preferably 10 nm to 200 nm, further preferably 10 nm to 100 nm. The particle size (d50) is the so-called median particle size, which refers to the particle size distribution measured by the laser diffraction scattering method, and the particle size at which 50% accumulation is reached when the total volume of the particles is set to 100% in the cumulative distribution.

[0125] -Other ingredients-

[0126] In addition to epoxy resin, curing agent, polymer component, and filler, the film adhesive may further contain an ion trapping agent (ion trapping agent), a curing catalyst, a viscosity modifier, an antioxidant, a flame retardant, and a colorant, etc., within the scope of not damaging the effect of the present invention. For example, other additives of International Publication No. 2017 / 158994 may be included.

[0127] It should be noted that, from the viewpoint of bonding reliability, the film-like adhesive preferably does not contain a colorant such as a dye or a pigment. In addition, it is also preferably in a form that does not contain a filler.

[0128] The total content of the epoxy resin and the polymer component contained in the film adhesive is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and also preferably 80% by mass or more.

[0129] -Thickness of film adhesive-

[0130] The thickness of the film adhesive is not particularly limited and can be appropriately set according to the purpose. The thickness of the film adhesive can be, for example, 1 μm to 30 μm, preferably 1 μm to 25 μm, preferably 1 μm to 20 μm, preferably 2 μm to 20 μm, preferably 3 μm to 20 μm, and preferably 4 μm to 20 μm. The thickness of the film adhesive can be measured by a contact / linear gauge method (desktop contact thickness measuring device).

[0131] <Manufacturing of Film Adhesive with Cut Die Film>

[0132] The method for producing the film-like adhesive with a cut wafer film is not particularly limited as long as a structure in which the cut wafer film and the film-like adhesive are laminated can be formed.

[0133] For example, a coating liquid containing an adhesive is applied to a release liner treated with a demolding agent, dried to form an adhesive layer, and the adhesive layer is laminated to a substrate to obtain a laminate having a substrate, an adhesive layer, and a release liner laminated thereon in sequence. In addition, a film-like adhesive-forming composition is applied to a release film (which has the same meaning as the release liner, but the expression is changed here for convenience) and dried to form a film-like adhesive on the release film. Next, the release liner is peeled off, the cut film exposed by the adhesive layer is brought into contact with the film-like adhesive, and the cut film is laminated to the film-like adhesive, thereby obtaining a film-like adhesive with a cut film having a substrate, an adhesive layer, a film-like adhesive, and a release film laminated thereon.

[0134] The bonding of the die cut film and the die bond film is preferably performed under pressure.

[0135] In the bonding of the above-mentioned wafer cutting film and the film adhesive, the shape of the wafer cutting film is not particularly limited as long as it can cover the opening of the annular frame, and is preferably circular. The shape of the film adhesive is also not particularly limited as long as it can cover the back of the wafer, and is preferably circular. The wafer cutting film is preferably larger than the film adhesive and has a portion of the adhesive layer exposed around the adhesive layer. In this way, it is preferred to bond the wafer cutting film cut into the desired shape to the film adhesive.

[0136] The film-like adhesive with a cut wafer film produced as described above is used after peeling off the release film.

[0137] The formation of the film-like adhesive will be further described.

[0138] Film-like adhesive can be obtained by using a composition (film-like adhesive forming composition (varnish)) formed by mixing the components constituting the film-like adhesive at a temperature at which the epoxy resin does not actually undergo heat curing to form a film. The order of mixing is not particularly limited. For example, resin components such as epoxy resin and polymer components can be mixed with a solvent as needed, and then a curing agent is mixed. In this case, as long as the mixing under the presence of a curing agent is carried out at a temperature at which the epoxy resin does not actually undergo heat curing, the mixing of the resin components in the absence of a curing agent can be carried out at a higher temperature.

[0139] The film formation using the film-like adhesive forming composition can be formed by, for example, applying the film-like adhesive forming composition on a release-treated substrate (also referred to as a release film or a peeling film) and drying it as necessary.

[0140] As the release film, any common release film may be appropriately used as long as it functions as a cover film of the obtained film-like adhesive, and examples thereof include release-treated polypropylene (PP), release-treated polyethylene (PE), and release-treated polyethylene terephthalate (PET).

[0141] As the coating method, a common method can be appropriately adopted, and examples thereof include methods using a roll knife coater, a gravure coater, a die coater, a reverse coater, and the like.

[0142] Drying may be performed by removing the organic solvent from the film-adhesive-forming composition to obtain a film-adhesive without substantially curing the epoxy resin, and can be performed, for example, by maintaining the composition at a temperature of 80° C. to 150° C. for 1 to 20 minutes.

[0143] The film-like adhesive may be formed by laminating the above-mentioned release film etc. on at least one surface. In this case, the release film does not constitute the film-like adhesive and is considered to be laminated on the film-like adhesive. That is, in the form of laminating the above-mentioned release film etc. on at least one surface of the film-like adhesive, when explaining the thickness of the film-like adhesive, the thickness does not include the thickness of the release film etc. That is, in the present invention, the thickness of the film-like adhesive is the thickness of the layer derived from the film-like adhesive forming composition.

[0144] From the viewpoint of more reliably suppressing the thermal curing of the epoxy resin, the film-like adhesive is preferably stored at a temperature of 10° C. or less before use.

[0145] The film-like adhesive with a cut wafer film of the present invention may be further laminated with a release film or the like.

[0146] The film-like adhesive with a cut crystal film of the present invention is made into such a laminated film, and a transparent film-like component (adherend) such as a transparent protective film can be tightly adhered to the film-like adhesive side of the laminated film, which is fixed by the cut crystal film, and the transparent film-like component is cut (cut) into a desired size together with the film-like adhesive. As a result, a transparent film-like chip with an adhesive layer cut into a desired size can be obtained on the cut crystal film. Then, the transparent film-like chip with the adhesive layer can be peeled off from the cut crystal film, and the transparent film-like chip can be assembled into an electronic component by the adhesive layer. The assembly into the electronic component is performed by thermocompression bonding, etc., and then the adhesive layer is thermally cured, thereby being accompanied by a curing reaction, such as a reaction of a solid curing agent, and the transparency of the adhesive can be improved.

[0147] The above-mentioned thermocompression bonding is performed at a temperature at which the epoxy resin does not actually undergo thermal curing, and as an example, the conditions are 70° C. and a pressure of about 0.3 MPa.

[0148] The above-mentioned thermosetting reaction can be carried out above the thermosetting starting temperature of the film-like adhesive. The thermosetting starting temperature varies according to the types of epoxy resin, polymer component and epoxy curing agent used, and cannot be generalized. For example, it is preferably 100°C to 180°C, and from the perspective of achieving short-time curing, it is more preferably 140°C to 180°C. If the temperature is lower than the thermosetting starting temperature, there is a tendency that the thermosetting reaction cannot be fully carried out and the strength of the adhesive layer is reduced. On the other hand, if the temperature of the curing reaction is too high, there is a tendency that the curing agent and additives in the film-like adhesive volatilize during the curing reaction and are easy to foam. In addition, the time of the curing treatment is preferably 10 minutes to 120 minutes, for example.

[0149] With regard to the above-described embodiment, according to the present invention, there is provided a method for manufacturing an electronic component as shown below.

[0150] A method for manufacturing an electronic component, the method comprising:

[0151] In the first step, a laminated body is obtained in which a transparent film-like member and a film-like adhesive with a cut-wafer film of the present invention are sequentially laminated.

[0152] The second step is to cut the transparent film member and the film adhesive integrally, thereby obtaining a transparent film chip with an adhesive layer on the cut film;

[0153] A third step is to remove the cut wafer film from the adhesive layer, and to thermally press-bond the transparent film-shaped chip with the adhesive layer to other members constituting the electronic component via the adhesive layer; and

[0154] In the fourth step, the adhesive layer is thermally cured.

[0155] The electronic component obtained by the above-mentioned production method has a structure in which the transparent film-like chip is assembled in the electronic component via a thermosetting body of the film-like adhesive.

[0156] In the present invention, the "transparent film chip" refers to a transparent film processed into a desired shape. Typically, a transparent film member such as a glass substrate or a transparent resin is cut into a desired shape in order to incorporate it into an electronic component.

[0157] An example of the electronic component is an image sensor (imaging element). In this case, the transparent film-like chip incorporated in the electronic component is preferably a protective film of a photodiode.

[0158] It should be noted that a preferred embodiment of the transparent film-like member is described above, and the present invention is not subject to any limitation of these embodiments except for the contents specified in the present invention. For example, as the above-mentioned electronic component, it is also preferred to cite components used in optical devices such as optical lenses, optical fibers, optical waveguides, optical isolators and semiconductor lasers.

[0159] Example

[0160] The present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to the following embodiments.

[0161] In the following description, room temperature refers to 25° C. In addition, “MEK” is methyl ethyl ketone, and “PET” is polyethylene terephthalate.

[0162] As each embodiment and comparative example, Figure 1 The film-like adhesive with a release film is shown.

[0163] [Production of cut-crystal film]

[0164] <Preparation of base material>

[0165] (Substrate X)

[0166] A zinc ionomer resin of an ethylene-methacrylic acid copolymer (trade name: Himilan 1855, manufactured by Du Pont-Mitsui Polychemicals Co., Ltd.) was melted at 200° C. and used with an extruder to prepare a substrate X having a thickness of 90 μm. One surface of the substrate X was subjected to a corona treatment.

[0167] (Base material Y)

[0168] A zinc ionomer resin of an ethylene-methacrylic acid copolymer (trade name: Himilan AM7326, manufactured by Du Pont-Mitsui Polychemicals Co., Ltd.) was melted at 200° C. and used with an extruder to prepare a substrate Y having a thickness of 90 μm. One surface of the substrate Y was subjected to a corona treatment.

[0169] (Base material Z)

[0170] An ethylene-methacrylic acid copolymer (trade name: NUCREL N0200H, manufactured by Du Pont-Mitsui Polychemicals Co., Ltd.) was melted at 200° C. and used with an extruder to prepare a substrate Z having a thickness of 90 μm. One surface of the substrate Z was subjected to a corona treatment.

[0171] <Cut Film A>

[0172] 65 parts by mass of butyl acrylate, 25 parts by mass of 2-hydroxyethyl acrylate and 10 parts by mass of acrylic acid were subjected to free radical polymerization, and then 2-isocyanatoethyl methacrylate was added dropwise and reacted to obtain an acrylic copolymer having a weight average molecular weight of 800,000. 3 parts by mass of polyisocyanate as a curing agent and 1 part by mass of 1-hydroxy-cyclohexyl-phenyl-ketone as a photopolymerization initiator were added to 100 parts by mass of the acrylic copolymer and mixed to obtain an adhesive layer composition.

[0173] Next, the adhesive layer composition was applied to a release liner treated with a release agent so as to have a dry film thickness of 10 μm, and dried at 120° C. for 3 minutes to obtain an adhesive layer. The adhesive layer was bonded to the corona-treated surface of the substrate X to prepare a cut wafer film A having a substrate and an adhesive layer with a release liner.

[0174] <Cut film B>

[0175] A cut film B was produced in the same manner as the cut film A except that the substrate to be used was changed to the substrate Y.

[0176] <Cut Film C>

[0177] A cut film C was produced in the same manner as the cut film A except that the substrate to be used was changed to the substrate Z.

[0178] [Preparation of film-like adhesive with cut-wafer film]

[0179] The components used in the preparation of the film adhesive are shown below.

[0180] <Materials used>

[0181] (Epoxy resin)

[0182] 828 (bisphenol A epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 190 g / eq, specific gravity 1.17)

[0183] ·ST-3000 (Hydrogenated bisphenol A type epoxy resin, manufactured by Nippon Steel Chemicals Co., Ltd.)

[0184] ·YDCN-703 (cresol novolac type epoxy resin, manufactured by Tohto Kasei Co., Ltd., epoxy equivalent 210 g / eq, molecular weight 1200, softening point 80°C)

[0185] (Phenoxy resin)

[0186] 1256 (phenoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 7500 g / eq)

[0187] (Urethane resin)

[0188] Dynaleo VA-9320M (urethane resin solution, weight average molecular weight: 120,000, Tg: 39°C, room temperature elastic modulus: 594 MPa, solvent: MEK / IPA mixed solvent, manufactured by TOYOCHEM Co., Ltd.) (referred to as VA-9320M in the table)

[0189] (Acrylic resin)

[0190] SG-P3 (acrylic resin, manufactured by Nagase ChemteX Co., Ltd., weight average molecular weight 850,000, glass transition temperature 10°C)

[0191] (Curing agent)

[0192] 2PHZ-PW (imidazole curing agent, manufactured by Shikoku Chemicals Co., Ltd.)

[0193] SI-150 (thermal cationic polymerization initiator, manufactured by Sanshin Chemical Co., Ltd.)

[0194] (Phenolic resin)

[0195] Milex XLC-LL (phenolic resin, manufactured by Mitsui Chemicals, Inc., hydroxyl equivalent 175 g / eq)

[0196] (Filling material)

[0197] RY-200 (nanosilica filler, manufactured by Japan AEROSIL Co., Ltd., particle size (d50): 12nm, Mohs hardness: 7Mohs, thermal conductivity: 1W / m·K)

[0198] ·S0-C2 (silica filler, manufactured by Admafine Co., Ltd., specific gravity 2.2 g / cm 3, Mohs hardness: 7Mohs, particle size (d50) 500nm, specific surface area 6.0m 2 / g)

[0199] <Example 1>

[0200] (Preparation of film adhesive)

[0201] 50 parts by mass of epoxy resin (trade name: 828, manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 190 g / eq, specific gravity 1.17) and 50 parts by mass of phenoxy resin (trade name: 1256, manufactured by Mitsubishi Chemical Corporation, bisphenol A type phenoxy resin, epoxy equivalent 7500 g / eq) were heated and stirred at 110° C. for 2 hours with MEK in a 1000 ml separable flask to obtain a resin varnish. Next, the resin varnish was transferred to another flask container, 1 part by mass of a curing agent (trade name: 2PHZ-PW, imidazole type curing agent, manufactured by Shikoku Chemicals Co., Ltd.) was added, and the mixture was stirred and mixed at room temperature for 1 hour, and then vacuum degassing was performed to obtain a mixed varnish. Furthermore, the obtained mixed varnish was applied to a PET film (release film) having a thickness of 38 μm and subjected to a demolding treatment, and heated and dried at 130° C. for 10 minutes to form a film-like adhesive layer having a length of 300 mm, a width of 300 mm, and a thickness of 20 μm. The obtained film-like adhesive with a release film was stored at a temperature below 10° C. After the above drying, the epoxy resin was not cured (hereinafter, unless otherwise specified, the same applies to other examples and comparative examples).

[0202] (Preparation of film-like adhesive with cut-wafer film)

[0203] Next, the wafer-cutting film B with release liner is cut into a circular shape that can be attached to cover the opening of the annular frame. Also, the film-like adhesive with release film is cut into a circular shape that can cover the back surface of the wafer.

[0204] Using a roller press, under the conditions of a load of 0.4 MPa and a speed of 1.0 m / min, the exposed slicing film B which was peeled off from the slicing film B with a release liner cut as described above was bonded to the film-like adhesive with a release film cut as described above, thereby producing a film-like adhesive with a slicing film having a substrate, an adhesive layer, a film-like adhesive and a release film layered in sequence. The film-like adhesive with a slicing film has a film-like adhesive formed on the adhesive layer of the slicing film having a substrate and an adhesive layer. In addition, in the film-like adhesive with a slicing film, the slicing film is larger than the film-like adhesive, and there is a portion of the slicing film exposed around the film-like adhesive.

[0205] <Example 2>

[0206] In the preparation of the film adhesive of Example 1, 1 mass part of SI-150 was used instead of 2PHZ-PW as a curing agent, and 3 mass parts of RY-200 were added to the mixed varnish as a filler. Otherwise, a film adhesive with a release film and a film adhesive with a cut-wafer film were obtained in the same manner as in Example 1.

[0207] <Example 3>

[0208] In the preparation of the film-like adhesive of Example 1, a film-like adhesive with a release film and a film-like adhesive with a cut wafer film were obtained in the same manner as in Example 1 except that 11 parts by mass of RY-200 was added to the mixed varnish as a filler.

[0209] <Example 4>

[0210] In the preparation of the film adhesive of Example 2, a film adhesive with a release film and a film adhesive with a cut wafer film were obtained in the same manner as in Example 2 except that 5 parts by mass of SO-C2 was added to the mixed varnish instead of RY-200 as a filler.

[0211] <Example 5>

[0212] In the preparation of the film-like adhesive with a cut film of Example 2, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 2 except that the cut film A was used as the cut film.

[0213] <Example 6>

[0214] In the preparation of the film-like adhesive with a cut film of Example 3, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 3 except that the cut film A was used as the cut film.

[0215] <Example 7>

[0216] In the preparation of the film-like adhesive with a cut film of Example 4, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 4 except that the cut film A was used as the cut film.

[0217] <Example 8>

[0218] In the preparation of the film adhesive of Example 5, 150 parts by mass of a urethane resin solution (VA-9320M) (including 50 parts by mass of a urethane resin) was used as the polymer component instead of the phenoxy resin (1256), the curing agent in the mixed varnish was 1 part by mass of 2PHZ-PW, and 35 parts by mass of RY-200 was added as a filler. Otherwise, a film adhesive with a release film and a film adhesive with a cut-wafer film were obtained in the same manner as in Example 5.

[0219] <Example 9>

[0220] In the preparation of the film-like adhesive of Example 5, a film-like adhesive with a release film and a film-like adhesive with a cut wafer film were obtained in the same manner as in Example 5 except that 50 parts by mass of ST-3000 was used instead of 828 as the epoxy resin.

[0221] <Example 10>

[0222] In the preparation of the film-like adhesive of Example 5, a film-like adhesive with a release film and a film-like adhesive with a cut wafer film were obtained in the same manner as in Example 5 except that 20 parts by mass of RY-200 was added to the mixed varnish as a filler.

[0223] <Example 11>

[0224] In the preparation of the film adhesive of Example 5, a film adhesive with a release film and a film adhesive with a cut wafer film were obtained in the same manner as in Example 5 except that the compounding amount of 828 in the resin varnish was 30 parts by mass and the compounding amount of 1256 was 70 parts by mass.

[0225] <Example 12>

[0226] In the preparation of the film adhesive of Example 2, a film adhesive with a release film and a film adhesive with a cut wafer film were obtained in the same manner as in Example 2 except that the compounding amount of 828 in the resin varnish was 60 parts by mass and the compounding amount of 1256 was 40 parts by mass.

[0227] <Comparative Example 1>

[0228] In the preparation of the film-like adhesive with a cut film of Example 1, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 1 except that the cut film A was used as the cut film.

[0229] <Comparative Example 2>

[0230] In the preparation of the film adhesive of Comparative Example 1, a film adhesive with a release film and a film adhesive with a cut wafer film were obtained in the same manner as in Comparative Example 1 except that 80 parts by mass of SO-C2 was added to the mixed varnish as a filler.

[0231] <Comparative Example 3>

[0232] In the preparation of the film adhesive of Example 1, 18 parts by mass of YDCN-703 was used instead of 828 as the epoxy resin, 100 parts by mass of acrylic resin (SG-P3) was used instead of phenoxy resin (1256) as the polymer component, and 1 part by mass of 2PHZ-PW and 15 parts by mass of Milex XLC-LL were used as curing agents. Except for this, a film adhesive with a release film and a film adhesive with a cut-wafer film were obtained in the same manner as in Example 1.

[0233] <Comparative Example 4>

[0234] In the preparation of the film adhesive of Comparative Example 3, the mixing amount of YDCN-703 was 50 parts by mass, the mixing amount of SG-P3 was 250 parts by mass, 2PHZ-PW was not mixed and 50 parts by mass of Milex XLC-LL was used as a curing agent, and 35 parts by mass of S0-C2 was added to the mixed varnish as a filler. Except for this, a film adhesive with a release film and a film adhesive with a cut-wafer film were obtained in the same manner as in Comparative Example 3.

[0235] <Comparative Example 5>

[0236] In the preparation of the film-like adhesive with a cut film of Example 2, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 2 except that the cut film C was used as the cut film.

[0237] <Comparative Example 6>

[0238] In the preparation of the film-like adhesive with a cut film of Example 3, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 3 except that the cut film C was used as the cut film.

[0239] <Comparative Example 7>

[0240] In the preparation of the film-like adhesive with a cut film of Example 4, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 4 except that the cut film C was used as the cut film.

[0241] <Comparative Example 8>

[0242] In the preparation of the film-like adhesive with a cut film of Example 8, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 8 except that the cut film C was used as the cut film.

[0243] <Comparative Example 9>

[0244] In the preparation of the film-like adhesive with a cut film of Example 9, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 9 except that the cut film C was used as the cut film.

[0245] <Comparative Example 10>

[0246] In the preparation of the film-like adhesive with a cut film of Example 10, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 10 except that the cut film C was used as the cut film.

[0247] <Comparative Example 11>

[0248] In the preparation of the film-like adhesive with a cut film of Example 11, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 11 except that the cut film C was used as the cut film.

[0249] <Comparative Example 12>

[0250] In the preparation of the film-like adhesive with a cut film of Example 12, a film-like adhesive with a release film and a film-like adhesive with a cut film were obtained in the same manner as in Example 12 except that the cut film C was used as the cut film.

[0251] For the film-like adhesive with release film and the cut films A to C obtained in the above-mentioned respective Examples and Comparative Examples, the storage modulus of the film-like adhesive at 60° C. and the storage modulus of the cut films at 60° C. were determined as follows.

[0252] [Measurement of storage modulus of film adhesive]

[0253] The release film was peeled off from the film adhesive with a release film obtained in each embodiment and comparative example, and the film adhesive was laminated to a thickness of 0.5 mm at 70°C using a laminator. The laminate was cut into 5 mm wide pieces as a measurement sample. The viscoelastic behavior of the film adhesive when the temperature was increased from 25°C to 80°C at a heating rate of 5°C / min under the tensile conditions of a chuck distance of 20 mm and a frequency of 10 Hz was measured using a dynamic viscoelasticity measuring device RSAIII (manufactured by TA Instruments), and the storage modulus E1 at 60°C was obtained.

[0254] [Measurement of Storage Modulus of Cut-Waste Film]

[0255] Cut films A to C were cut into 5 mm wide samples. The viscoelastic behavior of the cut films was measured under the conditions of a chuck distance of 20 mm and a tension frequency of 10 Hz and a temperature increase rate of 5°C / min from 25°C to 80°C, and the storage modulus E2 at 60°C was obtained.

[0256] It should be noted that the storage modulus of the substrate alone at 60° C. was measured, and the result was substantially the same as the storage modulus of the cut crystal film.

[0257] The film adhesives with cut wafer films obtained in the above-mentioned Examples and Comparative Examples were evaluated for light transmittance and chip flying after curing of the film adhesives as follows.

[0258] [Measurement of light transmittance of cured film adhesive]

[0259] After the film adhesive with the cut crystal film was heated and cured at 150°C for 1 hour, the cut crystal film was peeled off, and the parallel light transmittance of the film adhesive alone was measured in the wavelength range of 200nm to 1100nm using a spectrophotometer (manufactured by Hitachi High-Technologies Corporation, spectrophotometer U-4100 solid material measurement system), and evaluated using the parallel light transmittance at a wavelength of 400nm.

[0260] [Chip flying evaluation]

[0261] First, the film adhesive with the cut crystal film obtained in each example and comparative example was bonded to one surface of a glass wafer (material D263, 10 cm square, thickness 100 μm) at a temperature of 70° C. and a pressure of 0.3 MPa using a manual laminator (trade name: FM-114, manufactured by Technovision) at a temperature of 70° C. and a pressure of 0.3 MPa so that the film adhesive layer was in contact. Thereafter, a dicing frame (trade name: DTF2-8-1H001, manufactured by DISCO) was bonded to the region of the film adhesive to which the glass wafer was not bonded at room temperature and a pressure of 0.3 MPa using the manual laminator. Next, a dicing device (trade name: DFD-6340, manufactured by DISCO) equipped with a biaxial dicing blade (Z1: NBC-ZH2050 (27HEDD), manufactured by DISCO, Z2: NBC-ZH127F-SE (BC), manufactured by DISCO) was used to perform dicing from the glass wafer side in a manner to form a size of 2 mm×2 mm. 2500 chips were obtained by this cutting. The number of chips that flew out (peeled off) in the cut samples was counted, and the chip flying rate relative to the total number of chips was calculated (the number of chips that flew out / the total number of chips × 100). The obtained chip flying rate was substituted into the following evaluation criteria for evaluation.

[0262] -Evaluation Criteria-

[0263] AA: Chip flying rate is 0%

[0264] A: The chip flying rate is less than 1% of all chips

[0265] B: The chip flying rate is more than 1% and less than 3% of all chips

[0266] C: The chip flying rate is more than 3% of all chips

[0267] The above results are summarized in the table below. In the table below, the values ​​representing the mixing amounts of epoxy resin, polymer component, curing agent, and filler are in parts by mass. A blank column indicates that the component is not contained. The "Filler content" column records the content of the filler in the total solid content of the film adhesive.

[0268]

[0269]

[0270] The film adhesive with a cut die film of Comparative Example 1 did not satisfy the relationship of storage elastic modulus E1×E2≥7.0. The film adhesive with a cut die film of Comparative Example 1 caused chip flying during dicing.

[0271] In the film adhesives with cut wafer films of Comparative Examples 2 to 4, the light transmittance of the cured products of the film adhesives was 35% or less, and they did not show sufficient transparency. One reason for this is that the amount of filler in Comparative Example 2 was too large, and the acrylic resin and epoxy resin in Comparative Examples 3 and 4 were incompatible.

[0272] The film adhesives with cut wafer films of Comparative Examples 5 to 12 did not satisfy the relationship of storage elastic modulus E1×E2≥7.0. The film adhesives with cut wafer films of Comparative Examples 5 to 12 caused chip flying during dicing.

[0273] In contrast, the film adhesives with cut wafer films of Examples 1 to 12 satisfying the requirements of the present invention satisfy E1×E2≥7.0, and the light transmittance of the cured product of the film adhesive is 60% or more. It is known that if these film adhesives with cut wafer films are used, the chip flying out can be effectively suppressed during the dicing process, and sufficiently high transparency is exhibited after the curing reaction.

[0274] The present invention has been described in conjunction with its embodiments, but the applicant believes that, unless otherwise specified, the present invention is not limited to any details in the description and should be broadly interpreted without violating the spirit and scope of the invention as shown in the appended claims.

[0275] This application claims the priority based on Japanese Patent Application No. 2023-074875 filed in Japan on April 28, 2023, the contents of which are incorporated herein by reference as a part of the contents described in this specification.

[0276] Description of Reference Numerals

[0277] 10 Cutting film

[0278] 11. Substrate

[0279] 12 Adhesive layer

[0280] 20 Film adhesive

Claims

1. A film-like adhesive with a cut crystal film, comprising: a cut crystal film having a substrate and an adhesive layer; and a film-like adhesive disposed on the adhesive layer, The storage modulus E1 of the film adhesive at 60°C and the storage modulus E2 of the cut-crystal film at 60°C satisfy E1×E2≥7.0, wherein, The units of the storage modulus E1 and the storage modulus E2 are MPa, The cured product of the film-like adhesive has a light transmittance of 60% or more.

2. The film-like adhesive with a cut wafer film according to claim 1, wherein: The film-like adhesive contains an epoxy resin and a phenoxy resin.

3. The film-like adhesive with a cut wafer film according to claim 1 or 2, wherein: The film-like adhesive contains a filler, and the content of the filler is 10% by mass or less of the total solid content of the film-like adhesive.

4. The film-like adhesive with cut wafer film according to claim 3, wherein: The particle size d50 of the filler material is less than 500 nm.

5. The film-like adhesive with a cut wafer film according to any one of claims 1 to 4, wherein: The film adhesive contains a curing agent, and the curing agent is a thermal cationic polymerization initiator.

6. The film-like adhesive with a cut wafer film according to any one of claims 1 to 5, wherein: E1 is 0.1MPa~1.0MPa, and E2 is 10MPa~70MPa.

7. A method for manufacturing an electronic component, the method comprising: In a first step, a laminated body is obtained in which a transparent film-like member and the film-like adhesive with a cut wafer film according to any one of claims 1 to 6 are sequentially laminated. In a second step, the transparent film member and the film adhesive are cut integrally to obtain a transparent film chip with an adhesive layer on the cut film; A third step is to remove the cut wafer film from the adhesive layer, and to thermally press-bond the transparent film-shaped chip with the adhesive layer to other members constituting the electronic component via the adhesive layer; and In the fourth step, the adhesive layer is thermally cured.

8. The method for manufacturing an electronic component according to claim 7, wherein: The electronic component is an image sensor.

9. The method for manufacturing an electronic component according to claim 8, wherein: The electronic component has a structure in which the transparent film-like chip is incorporated as a protective film of a photodiode.